Strategi Pengelolaan Resiko Produksi Batik Pewarna Alami pada Koperasi Batik Ciwaringin - Icha Asaroh; Dini Selasi (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2026)
This study aims to analyze the risk management strategies in the production of natural dye batik at the Ciwaringin Batik Cooperative, Cirebon Regency. Ciwaringin Batik is recognized as one of the batik production centers that utilizes natural dyes derived from various plants, giving it significant cultural and environmental value. However, the production process of natural dye batik faces several risks, including color quality inconsistency, limited availability of natural raw materials, weather changes affecting the drying process, and limited workforce skills. These challenges may hinder business sustainability and the cooperative’s competitiveness. This research employs a descriptive qualitative approach through observation, interviews, and documentation studies to identify risk sources and management strategies. The findings indicate that production risk management is implemented through the diversification of raw material sources, enhancement of artisans’ skills through training programs, application of standard operating procedures (SOPs), and strengthening collaboration among the cooperative, farmers supplying natural dye materials, and other supporting stakeholders. These strategies effectively minimize potential production disruptions while maintaining the quality of environmentally friendly batik products. Therefore, effective risk management plays a crucial role in supporting the sustainability and development of the natural dye batik business at the Ciwaringin Batik Cooperative.